Tree bark as a bioindicator of air pollution in Navarra, Spain (Water, Air, & Soil Pollution, 1997)
During a two year research period from 1992 to 1993, samples of different species of trees were taken in 17 forest stands located in Navarra, Spain. From these samples, bark extracts were prepared in which the pH and the conductivity were measured. The health of the sampling trees was also evaluated by determining the degree of defoliation and decoloration of the canopies. The bark tissue analysis revealed the presence of an environmental acidity gradient that decreased from NW to SE. This coincides with the location of important sources of pollution and their course of transport and dispersion. On the other hand, in the samples of Quercus ilex a significant correlation between the pH and the defoliation levels (P<0.01, r = 0.62) was found. This fact reveals the potential usefulness of tree bark as a health bioindicator of trees.